Sexual dimorphism of the pelvic fins in Potamotrygon motoro (Batoid: Potamotrigonidae) - Pérez, Dante (2023)
Claspers in chondrichthyans are specialized elongations on the posterior side of the pelvic fins of males that are used for sperm transfer during copulation. The aim of this study was the description and characterization of the external morphology and skeletal components of the pelvic fin clasper of Potamotrygon motoro (Batoidea: Potamotrygonidae). The study included three juvenile specimens (2 males and 1 female) and two adult specimens (1 male and 1 female) from the Paraná River, Corrientes Capital. The samples were fixed in 10% formalin and processed using the diaphanization technique. The material was preserved in glycerol for observation. Macroscopically, sexual dimorphism is evident in males, through a structure in the posterior region called a clasper, with a slightly tapered conical shape, visible dorsally and ventrally. In diaphanous samples, the posterior cartilaginous elements can be distinguished, differentiating a propterygium and a basipterygium, which together with it are located the basal segments and the radial cartilages of the pelvic fins; however, only males develop a clasper or mixopterygian. In females, the only skeletal structures posterior to the basipterygium are small nodular elements (terminal cartilages). It was evidenced that these specimens in their first days of life already present the sexual dimorphism associated with the presence of clasper in males and its absence in females; however, juvenile males do not present the full development of the mixopterygian that forms the clasper.